Successful treatment of idiopathic knuckle pads with a combination of high-dose salicylic acid and urea topical keratolytics: A case report - Sogliani, Davide; Mura, Chiara; Tamborrini, Giorgio (Dermatology Reports, 2021)
Knuckle pads are benign subcutaneous and usually hyperkeratotic fibromas for which no specific treatments exist. Unspecific treatments are, most of the time, ineffective and a wait-and-see policy is often recommended to patients. However, especially in adolescents, knuckle pads are often poorly tolerated for cosmetic reasons, potentially causing embarrassment and social anxiety. Here we present the case of a young adult successfully treated with a combination of high-dose salicylic acid and urea topical keratolytics. In addition, we provide ideal diagnostic images obtained via high-resolution ultrasonography and histological features that can be used by medical practitioners to better distinguish knuckle pads from other proximal interphalangeal/ metacarpophalangeal joint diseases as also from other diseases inducing swelling of periarticular soft tissues.